Round table. Soft tissue sarcomas. Clinic and treatment: introduction - D'Auria, Agustín (Cirugía del Uruguay, 1973)
Soft tissue sarcomas, group of difficult to precision, include malignant tumors derived from mesenchymal tissues, housed in the space between the hypodermis and the periosteum or between the hypodermis and the parenchymal organs